Walking with Christ in the details of life - Morley, Patrick M. (Nashville : T. Nelson Publishers, 1992)
For men who feel half alive . . . half faithful . . . half obedient . . . half the totally committed Christian they long to be . . . men's movement pioneer Patrick Morley offers the motivation and inspiration for finding the abundant life they desire. Writing straight from the heart, Morley invites men to take a soul-searching look at how obedience to Christ in every area of life leads to a richer, deeper walk with God. In seventy-five short chapters, Morley covers topics like truth, prayer, the nature of God, the person of Jesus, materialism, eternal life, surrender, servanthood, expectations, power, suffering, holiness, character, and other important details that factor into wholehearted, biblical Christianity.
Part one: the God we want versus the God who is -- Part two: the escape from cultural Christianity -- Part three: our relationship with Christ -- Part four: the world of my motives -- Part five: the art of surrender -- Part six: the tools of surrender -- Part seven: responding to the struggles of daily life -- Part eight: developing my personal character -- Part nine: getting along with people.
Originally published: I surrender. Brentwood, Tenn. : Wolgemuth & Hyatt, 1990.
Includes index.
Keywords: Christian life; Obedience -- Religious aspects -- Christianity